2017
DOI: 10.3892/ol.2017.5602
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of growth factors in the treatment of hepatocellular carcinoma: The potentials of polysaccharides

Abstract: Abstract. Hepatocellular carcinoma (HCC) has become a leading cause of cancer-associated mortality worldwide and is thus of great concern. Although various chemotherapeutic drugs are currently used for the treatment of HCC, severe side effects associated with these treatments have prompted interest in novel therapies, including the use of certain biological macromolecules such as polysaccharides. Several studies have shown that polysaccharides have anticancer and antiproliferative effects on HCC. Vascular endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…A study has suggested that the transcription of FOXO genes is stimulated by FOXO3 itself but repressed by growth factors in a cell line model [24]. A wide variety of growth factors are highly expressed in liver cancer [25], A mixture of several transcriptional stimulators and repressors may control FOXO3 transcriptional regulation. Our observation about FOXO3 protein overexpression and activation in HCC samples nevertheless brought us a question, whether hepatic activation of FOXO3 in patients sufficiently supports hepatocellular carcinogenesis, or FOXO3 activation is just a consequence and secondary-effect during tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…A study has suggested that the transcription of FOXO genes is stimulated by FOXO3 itself but repressed by growth factors in a cell line model [24]. A wide variety of growth factors are highly expressed in liver cancer [25], A mixture of several transcriptional stimulators and repressors may control FOXO3 transcriptional regulation. Our observation about FOXO3 protein overexpression and activation in HCC samples nevertheless brought us a question, whether hepatic activation of FOXO3 in patients sufficiently supports hepatocellular carcinogenesis, or FOXO3 activation is just a consequence and secondary-effect during tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Botanical polysaccharides comply with many requirements of pharmaceutical excipients such as nontoxicity, stability, availability and renewability, they are extensively investigated for use in solid oral dosage forms (Wang et al., 2017 ; Chen et al., 2018 ). Meanwhile, botanical polysaccharides have been used for industrial applications, e.g.…”
Section: Applications Of Natural Polysaccharides In Tissue Engineerinmentioning
confidence: 99%
“…Growth factors (GF) are soluble proteins, which can participate in cell growth, proliferation, differentiation, migration, etc (Qian et al., 2017 ; Wang et al., 2017 ). They are derived from kinds of cells, including macrophages, fibroblasts, and so on, which coordinate immune responses, angiogenesis, and wound healing (Gallego-Muñoz et al., 2017 ; Duncan et al., 2018 ; Ishihara et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…As crosstalk mediators and potentiators of HCC, RNAi approaches have been developed to target the different growth factors in the vicinity of HCC. Growth factors such as VEGF and hepatocyte growth factor (HGF), and epidermal growth factor receptor (EGFR) have been observed to be overexpressed in many cancers including HCC, as they play a crucial role in different mechanisms involving tumor proliferation, metastasis and angiogenesis [49][50][51]. A shRNA targeting VEGF was designed to inhibit VEGF expression in HCC cells and liver tumor tissues.…”
Section: Targeting Communication With Extracellular Componentsmentioning
confidence: 99%